Effect of Fenugreek (Trigonella foenum graecum) Seeds supplementaion on Feed Intake and Some Biochemical Blood Parameters of Lactating Nubian Goats - A. Atta Elmnan, Balgees; E. E. Hamed, Hoida,; H. J. A., Gude; A. M., Abunikhaila; Fadel Elseed, A.M.A. (Journal of Veterinary Medicine and Animal Production, 2021)
The study aimed to investigate the effect of supplementing concentrate rations with four levels of crushed fenugreek seeds on feed intake and some biochemical blood parameters in Nubian goats’ at their early lactation stage. Twelve lactating Nubian goats were randomly distributed into four groups, three animals in each group using completely randomize design. Based on the supplement levels four rations were formulated: 0% (R0), 5% (R5), 10% (R10) and 15% (R15). The results indicated that feed intake was enhanced significantly (P≤0.001) with the increasing levels of supplement, accompanied with concomitant increase in the concentration of insulin hormone, whereas the level of glucose and leptin were decreased. Highly negative significant (P≤0.001) correlation between feed intake, glucose (r= - 0.81) feed intake and leptin (r= -0.75) were recorded. On the other hand, highly positive significant (P≤ 0.001) correlation were evident between feed intake and Insulin hormone (r= 0.83). Insulin correlated negatively with leptin (r= 0.63) and glucose (r= -0.68 (at (P≤0.001), while leptin correlated positively with glucose (r=0.61(at (P≤0.001). In conclusion, the increasing level of crushed fenugreek seeds in the concentrate ration of goats at their early lactation stage boosted feed intake, secretion of insulin hormone, regulated glucose physiologic secretion, while negatively affected leptin concentration.